Urgensi Berdirinya Bank Sentral Syariah Di Indonesia - Agus Pandoman (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2019)
Bank Indonesia has been established as a central bank that develops dual monetary policy. This paper identifies the challenges faced in Islamic financial policy that are different from other monetary policies. With a historical approach to law it can be concluded that there is still an opportunity for BI to develop Islamic finance in Indonesia by reinforcing its basic philosophy of returning to the real economy in the gold standard. Some suggestions for the implementation of the technical treatment of finance have been raised, but there is a need to accompany the implementation by stabilizing all Islamic-oriented central bank laws.